The Impact of Assigning Articles on The Critical Thinking Skills of Islamic Education Student - Nur'aliya, Hanny Rizqiyana; Manggali, Cahya Arum; Hayati, Dina Nur; Monita, Diana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to determine the effect of article assignment activities on the critical thinking of students studying Islamic Religious Education at the 7th semester level. A total of 142 students registered in the Islamic Religious Education study program at one of the universities in Yogyakarta were studied using quantitative methodology. The findings show a strong and affirmative relationship between article allocation and the development of critical thinking skills. This study found that article assignments accounted for 45% of the variation in critical thinking abilities among Islamic Religious Education students. In addition, this study also revealed that 37.6% of the variation in cognitive learning achievement could be caused by various factors. Developing critical thinking skills is very important for writing scientific articles, because it allows students to engage in discussions and analyze developing social issues. Article assignments also facilitate analysis, interpretation, and synthesis of knowledge, thereby becoming an advantage for students in the digital information age. Penelitian ini bertujuan untuk mengetahui pengaruh dari kegiatanpenugasan artikel terhadap berpikir kritis mahasiswa yang belajar Pendidikan Agama Islam di tingkat semester 7. Sebanyak 142 mahasiswa yang terdaftar di program studi Pendidikan Agama Islam di salah satu Perguruan Tinggi di Yogyakarta yang diteliti dengan menggunakan metodologi kuantitatif. Temuan menunjukkan hubungan yang kuat dan afirmatif antara alokasi artikel dan pengembangan kemampuan berpikir kritis. Studi ini menemukan bahwa tugas artikel menyumbang 45% dari variasi kemampuan berpikir kritis di kalangan mahasiswa Pendidikan Agama Islam. Selain itu, penelitian ini juga mengungkapkan bahwa 37,6% dari keragaman dalam prestasi belajar kognitif dapat disebabkan oleh berbagai faktor. Mengembangkan kemampuan berpikir kritis sangat penting untuk menulis artikel ilmiah, karena memungkinkan siswa untuk terlibat dalam diskusi dan menganalisis isu-isu sosial yang berkembang. Penugasan artikel juga memfasilitasi analisis, interpretasi, dan sintesis pengetahuan, sehingga menjadi keuntungan bagi siswa di era informasi digital. Kata Kunci: Penugasan Artikel; Kemampuan Berpikir Kritis; Mahasiswa Pendidikan Agama IslamKeywords: Article Assignment; Critical Thinking Ability; Islamic Religious Education Students